Reproductive notes and larval development of Macrogenioglottus alipioi (Anura: Odontophrynidae) from the northern Atlantic forest - Nascimento, Filipe Augusto C.; Aguilar, Anyelet Valencia [UNESP]; Pansonato, André; Lisboa, Barnagleison S.; Vilela, Bruno (Universidade de São Paulo. Agência de Bibliotecas e Coleções Digitais, 2022)
The neotropical monotypic genus Macrogenioglottus, described to enclose M. alipioi, is a forest leaf litter frog with a wide geographic distribution in eastern Brazil, despite being considered a rare species. Herein, we present some reproductive data of this species from a population of the north of the São Francisco River. Northeastern Brazil. We present information on the amplexus. egg clutch, advertisement, and release calls, along with a description of its larval development. Adults were observed only after heavy and continuous rains, in a temporary pond located inside the forest. Males call in chorus at the edge of the pond. The advertisement call consists of a pulsatile single note, with no substantial variation in relation to the other population of the species, but which promptly differs this genus from the remaining Odontophrynidae. The amplexus is axillary. One female deposited 298 pigmented eggs in a plastic bag. The tadpole reaches its larger size at Stage 39. being the largest tadpole within the family. At the end of metamorphosis, the froglet snout-vent length is equivalent to tadpole total length at stage 26-27, indicating substantial postmetamorphic growth until adulthood. Data on body size of males and females are also provided. The uniqueness of some larval traits and mainly on some call attributes supports the systematic distinction of Macrogenioglottus.
Notas reprodutivas e desenvolvimento larval de Macrogenioglottus alipioi (Anura: Odontophrynidae) no norte da Mata Atlântica
Keywords: Call; Egg clutch; Morphology; Ontogeny; Reproduction; Tadpole